The Perpetrators of the Theft of Minors at the Child Social Rehabilitation Center - Maulana, Firnanda Cindy; Rochmah, Nur; Agustina, Lella; Novanda, Galuh Dwi (Law Research Review Quarterly, 2020)
The development of the world in the recent era of globalization shows a very rapid development where can be felt various positive impacts such as the progress of science and technology. But in addition to the positive impacts, there are also negative impacts that can be felt, one of which is the rise of crime both in terms of quantity and quality. The crime does not only involve adults, but also children. Children as part of the younger generation who are potentials and successors of the ideals and struggles of the nation which in fact have a strategic role and special characteristics and traits, require guidance and protection in order to ensure physical, psychological, and sociological growth and development in a balanced manner. Children grow by analyzing the condition of the surrounding environment and absorbing what they see and feel. Crime cases involving children as perpetrators carry their own phenomena. One of the most common crimes committed by children is theft, with various motives and modus operandi. This observation was conducted to determine the impact of crimes involving children as perpetrators, what factors drive the child to commit these crimes, as well as how the attitude of the surrounding community.